Boron- and oxygen-doped π-extended helical nanographene with circularly polarised thermally activated delayed fluorescence - Venugopal, Geethu; Kumar, Viksit; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Khan, Abujunaid; Gonnade, Rajesh; Kumar, Jatish; Santhosh Babu, Sukumaran (Chemistry-A European Journal, 2024)
Helical nanographenes have garnered substantial attention owing to their finely adjustable optical and semiconducting properties. The strategic integration of both helicity and heteroatoms into the nanographene structure, facilitated by a boron-oxygen-based multiple resonance (MR) thermally activated delayed fluorescence (TADF), elevates its photophysical and chiroptical features. This signifies the introduction of an elegant category of helical nanographene that combines optical (TADF) and chiroptical (CPL) features. In this direction, we report the synthesis, optical, and chiroptical properties of boron, oxygen-doped pi-extended helical nanographene. The pi-extension induces distortion in the DOBNA-incorporated nanographene, endowing a pair of helicenes, (P)-B2NG, and (M)-B2NG exhibiting circularly polarized luminescence with glum of -2.3x10-3 and +2.5x10-3, respectively. B2NG exhibited MR-TADF with a lifetime below 5 mu s, and a reasonably high fluorescence quantum yield (50 %). Our molecular design enriches the optical and chiroptical properties of nanographenes and opens up new opportunities in multidisciplinary fields. B, O-doped pi-extended helical nanographene has been explored for its optical and chiroptical properties. The presence of helical and nanographene segments stabilize the helicity and imparts tunable optical properties. Helical nanographene display circularly polarized thermally activated delayed fluorescence. image
Keywords: circularly polarized luminescence; DOBNA; dual emission; nanographene; TADF

(Chiro)optical Properties of π-Extended Spiro-Double Carbo[7]helicene - Kumar, Viksit; Dongre, Sangram D.; Vandhanam, Aparna; Jadhav, Ashok Badrinarayan; Kumar, Jatish; Babu, Sukumaran Santhosh (Journal of Physical Chemistry Letters, 2025)
Helical nanographenes are a fascinating class of pi-extended chiral nanocarbons, where structural helicity imparts intrinsic chirality and unique optoelectronic properties to the rigid carbon framework. In this work, we synthesized a hexa-peri-hexabenzocoronene-based pi-extended spiro-double carbo[7]helicene. The helical distortion of the structure was unambiguously confirmed by X-ray crystallography. The optical properties were explored through UV-Vis absorption, fluorescence, and phosphorescence measurements, complemented by density functional theory (DFT) calculations. Remarkably, the pi-extended spiro-double carbo[7]helicene exhibited thermally activated delayed fluorescence (TADF) at room temperature and phosphorescence at low temperatures. Chiral HPLC successfully resolved the enantiomers into three fractions: (PP), (MM), and the meso forms (PM)/(MP), and chiroptical studies of the pure enantiomers revealed a moderately high g lum value of 1.58 x 10-3. Finally, the origin of the observed dissymmetry factors was rationalized by analyzing the transition electric dipole moments (TEDM) and transition magnetic dipole moments (TMDM) derived from time-dependent density functional theory (TD-DFT) calculations.

Chiroptical amplification of [7]-helicene nanographene by additional helical chirality - Dongre, Sangram D.; Venugopal, Geethu; Kumar, Viksit; Badrinarayan Jadhav, Ashok; Kumar, Jatish; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
Nanographenes have captivated scientific interest since the pioneering discovery of graphene. Recently, attention has shifted towards exploring chiral and nonplanar nanographenes, for their distinct optical, chiroptical, and electronic properties. Despite the growing acceptance of helicenes, the research on inducing helical chirality on pi-extended derivatives to boost chiroptical properties remains unattended. In our study, we introduce a new pi-extended [7]-helicene resulting from the condensation of diamines with 3,6-dibromophenanthrene-9,10-dione, complemented by two hexabenzocoronene arms in the periphery. Notably, the nanographene containing binaphtho-[1,4]diazocine, compared to the corresponding phenazine, exhibits a remarkable average 2.5, 5, and 10-fold enhancements in quantum yield, dissymmetry factor, and brightness, respectively, when measured in five different solvents. These improvements underscore the significance of the induced helical chirality by the antiaromatic binaphtho-[1,4]diazocine in influencing the chiroptical properties of the helical nanographene. Our research represents a significant stride toward unlocking the potential of pi-extended helicenes and lays the groundwork for further exploration in designing and synthesizing new chiral nanomaterials.
Keywords: circularly polarised luminescence; dissymmetry factor; helicene; nanographene; quantum yield

Regioisomeric π-extended nanographene with long-lived phosphorescence afterglow - Kumar, Viksit; Venugopal, Geethu; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Gonnade, Rajesh; Kumar, Jatish; Ruer, Paul C.; Hupp, Benjamin; Steffen, Andreas; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
The cutouts of graphene sheets, particularly those with a nonplanar topology, present vast opportunities for advancement. Even a slight deviation from the planar structure can lead to intriguing (chiro)optical features for helically twisted nanographenes. In this context, we introduce two regioisomeric pi-extended nanographenes that exhibit distinct excited-state characteristics. The helicene structure and the photophysical features can be easily tuned by changing the connecting position of the nanographene to the carbazole core (2,7- and 3,6-). Single-crystal X-ray diffraction analysis confirmed the formation of nanographenes with bent and helical conformations. Both derivatives exhibited thermally activated delayed fluorescence at room temperature and phosphorescence at low temperatures. Notably, the nanographene with the bent structure displayed an impressive red afterglow lasting over 30seconds, in contrast to the very weak afterglow observed in the helical structure. DFT calculations revealed the existence of an isoenergetic higher triplet state (T-8) and comparatively weak spin-orbit coupling (T-1-S-0), thereby enabling the bent nanographene to exhibit a long-lived component and strong afterglow. Our findings highlight the significance of regioisomeric nanographenes with exceptional optical properties and offer a deeper understanding of the structure-property relationship in nonplanar nanographenes.
Keywords: Afterglow; CPL; Helicenes; nanographene; Phosphorescence; TADF